Resurrection of Pseudorabdion torquatum (A.M.C. Duméril, Bibron & A.H.A. Duméril, 1854), a former synonym of P. longiceps (Cantor, 1847) (Colubridae: Calamariinae) from Sulawesi, Indonesia - Vogel, Gernot; Amarasinghe, A. A. Thasun; Ineich, Ivan (Zootaxa, 2016)
The colubrid snake species Pseudorabdion torquatum is resurrected from the synonymy of P. longiceps. Out of the three syntypes, only two were located and examined at Muséum national d’Histoire naturelle, Paris, France (MNHN-RA). Pseudorabdion torquatum differs from P. longiceps in having a larger SVL (227.0 mm vs. 132.0–193.0 mm in males); higher number of ventral in males, 141 (vs. 127–139); lower number of ventrals in females, 137 (vs. 139–145); lower number of subcaudals in both sexes, 12–17 (vs. 17–30); and six supralabials (vs. five). Pseudorabdion torquatum is thus regarded as a valid and endemic species to Sulawesi. The species is here redescribed and a lectotype is designated. Furthermore we provide an English translation of the original description of Rabdion torquatum which was originally written in French. Thus, besides unconfirmed records of P. longiceps from Sulawesi, there is a single known congener from that island, P. sarasinorum